Body Image and Depression in Emerging Adulthood Women - Christine Angelia Lubalu; Mariana Dinah Charlota Lerik; Juliana M. Y. Benu (Universitas Nusa Cendana, 2022)
The emerging adulthood phase is a phase of individual development between the ages of 18 and 25. This period is synonymous with changes that women will experience. Women receive a powerful message about their physical appearance from the environment, which plays a role in shaping their perception of their body image. Body image dissatisfaction arises if their perception does not correspond to the ideal appearance criteria. This study aims to see the relationship between body image and depression. This type of quantitative research uses a descriptive method involving 381 women between the ages of 18 and 25. Based on the results of the analysis of research data, it shows that the body image variable has a very high category and the depression variable is at the depression level. So there is a positive relationship between body image and depression.